Telaah Nilai Gotong Royong pada Fabel untuk Pendidikan Karakter di Sekolah Dasar - Imah, Rojimah; Rochmiyati, Siti; Yuniharto, Bonifatius Sigit (Universitas Muhammadiyah Magelang, 2022)
The type of literature that is seen as slick and useful for strengthening character education is fable. Fable is a type of fairy tale that raises the theme of animals as a play like humans who can talk, socialize, and behave like ordinary humans. In fables, the teachings of character values ​​are implicitly presented which are based on the intrinsic elements of the fable. The purpose of this research is to explore and describe the value of gotong royong contained in the fable text entitled Three Brothers, the Clever Crow, Four Friends Against Robbers, Pelican Girls, and United Fighting Crime by using a qualitative descriptive approach to systematically describe the value of gotong royong in fable texts. Meanwhile, for research data sources, namely words, sentences, or paragraphs that contain the value of the gotong royong character. The research data collection techniques were listening, note-taking, and documentation techniques. Data analysis for this study used content analysis techniques on fable texts. The focus of the object of this research is the value of mutual cooperation contained in the fable text which is then presented in the form of discussion analysis. Based on the results of the existing analysis, it shows that there are elements of mutual cooperation character values ​​contained in the five fable texts, namely cooperation and mutual assistance. Mutual cooperation will foster loyal friends and kinship. In order for mutual cooperation to run well, deliberation and consensus are needed and understanding the goals to be achieved.